The International Pulsar Timing Array second data release: Search for an isotropic gravitational wave background. Issue 4 (19th January 2022) - Antoniadis, J; Arzoumanian, Z; Babak, S; Bailes, M; Bak Nielsen, A-S; Baker, P T; Bassa, C G; Bécsy, B; Berthereau, A; Bonetti, M; Brazier, A; Brook, P R; et al.
ABSTRACT: We searched for an isotropic stochastic gravitational wave background in the second data release of the International Pulsar Timing Array, a global collaboration synthesizing decadal-length pulsar-timing campaigns in North America, Europe, and Australia. In our reference search for a power-law strain spectrum of the form h_c = A(f/1 yr^-1)^α , we found strong evidence for a spectrally similar low-frequency stochastic process of amplitude A = 3.8^+6.3_-2.5× 10^-15 and spectral index α = −0.5 ± 0.5, where the uncertainties represent 95 per cent credible regions, using information from the auto- and cross-correlation terms between the pulsars in the array. For a spectral index of α = −2/3, as expected from a population of inspiralling supermassive black hole binaries, the recovered amplitude is A = 2.8^+1.2_-0.8× 10^-15 . None the less, no significant evidence of the Hellings–Downs correlations that would indicate a gravitational-wave origin was found. We also analysed the constituent data from the individual pulsar timing arrays in a consistent way, and clearly demonstrate that the combined international data set is more sensitive. Furthermore, we demonstrate that this combined data set produces comparable constraints to recent single-array data sets which have more data than the constituent parts of the combination. Future international data releases will deliver increased sensitivity to gravitational wave radiation, and significantly increase the detection probability.